Performance Evaluation of Image Registration Using Multiple Novel Algorithms - Sunanda Gupta, Jyoti Verma, Shaveta Thakral, Pratima Manhas (International Journal of Advanced Science and Technology, 2020)
This paper describes the gist of the research work carried out in the area of image registration process. It summarizes the concluding remarks drawn from the algorithms based on Fuzzy C-means (FCM), Speeded-Up Robust Feature (SURF), Ant Colony Optimization (ACO), Powell Algorithm to consolidate the research work. It also explores the possible extension in the proposed novel approaches and methodology for an easy and efficient image registration techniques and scope for future work.Keywords: Image registration; Fuzzy C-means (FCM); Speeded-Up Robust Feature (SURF); Ant Colony Optimization (ACO); Powell Algorithm, Entropy; Bi-preserving Histogram Equalization (BBHE); Image Enhancement, Correlation.